Serum peptidome variations in a healthy population: reference to identify cancer-specific peptides. - Kun He (Public Library of Science (PLoS), 2013)
The emergence of mass spectrometry (MS)-based signatures as biomarkers has generated considerable enthusiasm among oncologists. However, variations in normal individuals also exist, and a better understanding of serum peptide patterns of healthy individuals will be important for further exploring disease-specific serum peptide patterns. Following development of a serum peptide pattern platform, we analyzed 500 serum samples obtained from healthy individuals. Samples from breast (n = 84), lung (n = 70), and rectal (n = 30) cancer patients were also examined. Extensive data analysis revealed negligible contributions of age to serum peptide patterns except in healthy individuals between 20-30 and 60+ years of age. Gender-related variations in the serum patterns of healthy individuals were only observed in 20-30 year-old individuals. Our results revealed substantial variation in individual peptide profiles, but 65 peptides were detected at a 20% higher frequency in the healthy population. A peptide profile was developed for each type of cancer, containing 10 discriminating peptides not prevalent in healthy individuals. Sequence identification of 111 signature peptides revealed that they fell into several tight clusters and most were exopeptidase products of serum resident proteins. We have obtained a MS-based serum peptide profile for healthy individuals, providing a reference for observing the occurrence of cancer-specific peptides.